“Youth are experts in what they need”: experiences and best practice in co-designing and implementing Fast-PrEP, a novel PrEP service for adolescents and youth in Cape Town, South Africa - Bennin, Fiona; Fynn, Lauren; Fuzile, Pamela; Yola, Ntando; Julies, Robin; Sindelo, Siyaxolisa; Madubela, Ndumiso; Vundhla, Prisca; Mpanda, Yolanda; Jonas, Mbali; Bekker, Linda-Gail; Rousseau, Elzette (Frontiers in Public Health, 2024)
IntroductionDefining the prevention needs, motivations, and gender dynamics influencing adolescent and young people’s (AYP’s) healthcare access is a key component to successful PrEP (pre-exposure prophylaxis for HIV prevention) implementation. WHO encourages a strong people-cantered approach to healthcare delivery, and this is particularly emphasized for HIV services. Enhanced youth engagement is needed to ensure that interventions are tailored to the specific needs and preferences of youth populations.DescriptionFast-PrEP is an implementation science project providing PrEP (oral, vaginal ring, and injectable) to adolescents and young people (15–29 years old) in Cape Town, South Africa. In 2020, during the planning phase of this project, a Youth Reference Group (YRG) was established to guide, co-create, monitor, and evaluate the implementation of PrEP delivery. From March to October 2023, we conducted four focus group discussions with thirty YRG members, and seven interviews with project implementers (including clinical and research staff). This study aimed to explore real-time experiences of young people and staff members and provide recommendations for best practices when setting up and engaging with YRGs.FindingsOverall, young people described their experience of being involved in the YRG as empowering. Young people felt that their voices and needs were valued when seeing their input put into action or witnessing their designs in demand creation campaigns. Young people felt that being consulted was not for tokenistic reasons, but their contribution was valuable and considered young people’s sexual health needs. Best practices included involving the YRG in every aspect of the project design and implementation, being flexible around young people’s schedules, and having engagements in spaces that are easily accessible and safe for key populations. Staff recommended upskilling the youth members in knowledge around HIV and certain ‘soft skills’ such as building self-confidence and communication skills. It was also recommended that all research and clinical staff need ongoing training and sensitization on the importance and value of youth engagement.ConclusionThe involvement of young people in the co-creation of Fast-PrEP services in all phases of service provision, has been effective in assisting to provide youth appropriate PrEP services.